Efficiency of Public Sector Organizations: Perspectives from Theories of Bureaucracy - ERKOC, Taptuk Emre (Journal of Advanced Research in Law and Economics; Vol 4 No 2 (2013): JARLE Volume IV Issue 2(8) Winter 2013, 2016)
Economic insights on the provision of public goods and services by public sector organizations went hand in hand with probing questions on the efficient allocation of resources within them concerning neo-classical assumptions on the theory of firm (Coase 1937, Alchian and Demsetz 1972). The rationale behind the unprecedented divergences from the neo-classical firm postulations on the basis of not-to-operate at the efficient production frontier has attracted attentions of researchers working not only on the private firms but also on the public sector. This paper investigates theoretical underpinnings of efficient allocation of resources within public sector organizations on the basis of a variety of arguments. Before examining the (in)efficient usage of resources in the public sector that is mostly based on the theory of bureaucracy, methodological and practical challenges to measure the efficiency performances of public intuitions are visited. Subsequently, institutional framework on the public provision of goods and services is scrutinized referring particularly to the discussion on incentive schemes and efficiency.
Keywords: efficiency, government output, public sector organizations, bureaucracy